2015
DOI: 10.1186/s40959-015-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myocardial dysfunction in cardiac morbidity and all cause mortality in childhood cancer subjects treated with anthracycline therapy

Abstract: Background: Subacute cardiotoxicity, consisting of acute myocyte damage and associated left ventricular dysfunction, occurs early during anthracycline therapy. We investigated the impact of myocardial dysfunction, defined herein by a shortening fraction (SF) < 29 % at any time during or after anthracycline therapy, on late onset cardiomyopathy and all-cause mortality, among childhood cancer survivors exposed to anthracyclines. In addition, we sought to identify subpopulations of subjects at highest risk for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Additionally, the risk of mortality was also stated to be increased 7-fold in these patients. 32 Similar to previous studies, the current study also revealed that consistent with the subclinical left ventricular myocardial dysfunction, the TDI-derived MPI and IVRT values were higher in CCSs who received a cumulative dose > 300 mg/m 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the risk of mortality was also stated to be increased 7-fold in these patients. 32 Similar to previous studies, the current study also revealed that consistent with the subclinical left ventricular myocardial dysfunction, the TDI-derived MPI and IVRT values were higher in CCSs who received a cumulative dose > 300 mg/m 2 .…”
Section: Discussionsupporting
confidence: 89%
“…The chemotherapeutic use of anthracyclines is limited by their capacity to induce dose-dependent cardiotoxicity (Gianni et al 2008), leading to development of heart failure and death(Gianni et al 2008; Toro-Salazar et al 2015). Efficacy and toxicity of anthracycline agents is highly variable in humans, reflecting the genetic diversity of patient populations as well as gender differences (Franco et al 2011; Lipshultz et al 2015).…”
mentioning
confidence: 99%